Una polèmica prosòdica a l'Acadèmia de Bones Lletres de Barcelona - Rafanell, August (Caplletra. Revista Internacional de Filologia, 2015)
August Rafanell presents and discusses a prosodic controversy that took place in the Acadèmia de Bones Lletres of Barcelona in the later xviii century. The controvers, on interest for the history of orthographic and prosodic issues, demonstrates the acceptance, by some important enlightened men, of the secessionist theses that were imposed in the xviii century on the Valencian people.